Transportation capacity for patients with highly infectious diseases in Europe: a survey in 16 nations. (April 2019) - ,; Vetter, Norbert; Kojouharova, Mira; Parmakova, Kremena; Skinhoej, Peter; Siikamaki, Heli; Perronne, Christian; Adrami, Olga; Lambert, John; Lanini, Simone; Hemmer, Robert; Borg, Michael; et al.
Abstract: Highly infectious diseases (HIDs) are defined as being transmissible from person to person, causing life-threatening illnesses and presenting a serious public health hazard. In most European Union member states specialized isolation facilities are responsible for the management of such cases. Ground ambulances are often affiliated with those facilities because rapid relocation of patients is most desirable. To date, no pooled data on the accessibility, technical specifications and operational procedures for such transport capacities are available. During 2009, the 'European Network for HIDs' conducted a cross-sectional analysis of hospitals responsible for HID patients in Europe including an assessment of (a) legal aspects; (b) technical and infrastructure aspects; and (c) operational procedures for ground ambulances used for HID transport. Overall, 48 isolation facilities in 16 European countries were evaluated and feedback rates ranged from 78% to 100% ( n  = 37 to n  = 48 centres). Only 46.8% (22/47) of all centres have both national and local guidelines regulating HID patient transport. If recommended, specific equipment is found in 90% of centres (9/10), but standard ambulances in only 6/13 centres (46%). Exclusive entrances (32/45; 71%) and pathways (30/44; 68.2%) for patient admission, as well as protocols for disinfection of ambulances (34/47; 72.3%) and equipment (30/43; 69.8%) exist in most centres. In conclusion, the availability and technical specifications of ambulances broadly differ, reflecting different preparedness levels within the European Union. Hence, regulations for technical specifications and operational procedures should be harmonized to promote patient and healthcare worker safety.